Ultrastructural analysis of Coarazuphium formoso (Coleoptera: Carabidae, Zuphiini), a new Brazilian troglobitic beetle - Pellegrini, Thaís Giovannini; Ferreira, Rodrigo Lopes (Zootaxa, 2011)
It is described Coarazuphium formoso sp. n., from male and female specimens collected in Barriguda cave and Calor de Cima cave, both in the municipality of Campo Formoso (Bahia, Brazil). The most striking difference between C. formoso and other species of the genus is the presence of three pairs of setae on the dorsal surface of the head close to the posterior margin, while the other species have only one or two pairs. Species from this genus showed advanced troglobiomorphic characters in comparison to other Brazilian cave beetles. Characters as increased extra-optic sensory structures, and the presence of particular sensilla, and sensory and gustatory receptors were not detected under routine microscopy but required ultrastructural scrutiny. Similar analyses are needed in other epigean Zuphiini species for better interpreting their functional meaning.